The Utility of a Master of Business Administration Degree in Plastic Surgery: Determining Motivations and Outcomes of a Formal Business Education Among Plastic Surgeons - Lee, Cody S. (Plast Reconstr Surg Glob Open, 2018)
BACKGROUND: With the increasing complexity of health care, the knowledge of business in medicine is growing more valuable. Plastic surgeons in all practice settings are constantly forced to navigate endeavors that could be better faced with the leadership, management, and administrative skills honed through a formal business education. The purpose of this study was to gather data and draw conclusions related to the motivations and outcomes of plastic surgeons with a Master of Business Administration degree (MBA). METHODS: An online survey was distributed to plastic surgeons in the United States who have earned an MBA. The survey was divided into 4 main sections: demographics, MBA program description, objective assessment, and subjective assessment. RESULTS: The majority of plastic surgeons with an MBA are in practice at an academic medical center. The 2 most popular tracks of completing the degree are during medical school and after 5 years of practice. A large proportion of plastic surgeons with an MBA experienced changes in their existing career position, namely in patient care and business roles outside of clinical practice. The most important skills surgeons subjectively felt they had improved as a result of their business education were in the areas of leadership, management, and administration. CONCLUSIONS: Overall, all the plastic surgeons felt that their MBA experience met their expectations and would recommend the degree to fellow physicians. Prime motivations included adding a new dynamic to their existing career, satisfying entrepreneurial drive, and gaining credibility in business, with monetary gains being low on the list.